Individual peculiarities of long jump technique of skilled athletes - Kozlova, E.; Wei, W.; Kozlov, K. (Journal of Physical Education and Sport, 2020)
The objective of the article is to identify the individual biomechanical characteristics of the long jump technique of skilled athletes. Material and methods. In furtherance of this objective of the study, the following methods were used: analysis of scientific and methodical literature and Internet; video shooting; biomechanical computer-based video analysis; methods of mathematical statistics. Two athletes, representatives of Ukraine and China, participated in the studies. The technology for biomechanical computer-based video analysis included two main stages: shooting with a video camera and processing the resulting videograms by means of "Dartfish", "Motion Analysis Tools" and "BioVideo" specialized software. Results. A comparative analysis of the individual long jump technique of two athletes allowed to reveal statistical differences in eight biomechanical indices, which was confirmed by the Mann-Whitney test at a level of p <0.05. Conclusions. For further technical improvement, athletes need to focus on those individual characteristics of technical skills that are the cornerstone of their success and ultimately provide the achievement of high sports results.